Heart of Darkness - Conrad, Joseph. author.
XI, 315 p.
Keywords: Written several years after Conrad's grueling sojourn in the Belgian Congo, the novel tells the story of Marlow, a seaman who undertakes his own journey into the African jungle to find the tormented white trader Kurtz.